TECHNOLOGY OF SELF-DETERMINED LEARNING AS A NEW FORMAT OF CONTINUING PROFESSIONAL EDUCATION OF TEACHERS - G. A. Ignatieva; O. V. Tulupova; S. V. Matchinа (Образование и наука)
Introduction. Continuing professional education (CPE) is a strategic resource of cardinal transformations, which are currently taking place in education. The essence of such transformations generally consists in necessary rejection of a subject-information learning model and transition to designing the model of vocational self-development and self-determination.The aim of this research was to reveal the essence of teachers’ professional development as the process of positional self-determination and formation of managerial position. The hypothesis of the study consists in the assumption that the technology of self-determined learning is the institutional form of mastering and implementing the practice of CPE for teachers as a practice of human potential development in the professional and anthropological self-determination of an adult learner.Methodology and research methods. The methodological basis of the study was the comparative educational strategy of CPE, which is embodied in the model of self-determined adult education, focused on the formation of the human ability to manage their own development in an unstable world through the development of new types of cultural thinking and behaviour. The methods of research of teachers’ management position included the system of the following initiatives: interviews, results of group reflections, content-analysis, methods of included observation using video recording of training sessions and educational products.Results and scientific novelty. The complex of diagnostic technologies allowed the authors to establish management positions of teachers (implementer, leader or strategist) and their ability to design the paths of own development and to organise the system of managerial challenges. As the most adequate technological scheme of self-determined learning, the authors tested the mechanism of projectresource management, which regulates the learner’s movement in the educational space from actions carried out in a particular situation in accordance with the circumstances to an activity determined by a local goal, then to the reflection of own activity elevating to the status of a new norm, and, finally, to the reflection of changes in their own position. It was established that the developmental trajectory of human potential in professiogenesis starts from mastering the subject and means of activity (implementer) and passes through building up funds in transforming a special subject of activity (leader) towards designing new standards of means and subject of activity (strategist).The authors introduce the concept of “anthropological self-determination of an adult in the educational process” as the process and the result of formation of own managerial position and development of a new identity in changing life circumstances.Practical significance of the present research is determined by the possibility of designing educational programmes, which ensure co-organisation of adult students in a single event-activity space based on the mechanisms of project-resource management through the system of managerial challenges.